Upaya Meningkatkan Kemampuan Komunikasi Statistika Melalui Pemberian Praktikum Pengolahan Data Berbantuan Komputer Pada Mahasiswa Prodi Pendidikan Matematika Stkip Garut - Sundayana, Rostina (Mosharafa: Jurnal Pendidikan Matematika, 2012)
In general students assume that statistics is scary enough course because the material requires a lot of counting. The purpose of this research is to compare Statistical communication ability between students who received MS Excel with students who received SPSS. The research method is experiment method by taking two classes as research samples. The first experiment class received MS Excel and the second experiment class received SPSS. The research materials include two test average of the dependent samples, two test average of independent samples, one way ANOVA test, regression, and simple correlation. The research results by using independent t-test, one way ANOVA, two-way ANOVA, as well as further Post Hoc test using Tukey HSD test with significant level of 0.05 conclude that: 1) Statistical communication ability of students who got MS Excel was better than those who got SPSS. 2) The increase in statistical communication ability of students who got MS Excel is better than those who got SPSS. 3) The increasing achievement of statistical communication, based on students' early capability (low, average, high), of those students who got MS Excel was better than those who got SPSS for the students who have low and average level. For students who have high level there was no significant difference in students who got MS Excel than those who got SPSS. 4) There was no interactive influence between learning model given and students early capability toward statistical communication ability.